The Mediating Role of Customer Satisfaction in the Relationship between Brand Image and Product Quality and Customer Loyalty: Shopee e-commerce Case Study - Iqbal, M. Ali; Parwoto, Parwoto; Abidin, Zaenal (Jurnal Manajemen Bisnis, 2024)
Business competition has become very tight and marketing is the main key for a business to run well. This causes many business people to do their marketing via the internet and generate sales, hence the emergence of online stores (electronic commerce). Shopee is one of the most used and visited e-commerce sites in Indonesia. In the first quarter of 2023, Shopee e-commerce was ranked first among the first visitors compared to other e-commerce. In this regard, researchers are interested in conducting research with the title The Mediating Role of Customer Satisfaction in the Relationship between Brand Image and Product Quality and Customer Loyalty (Case Study of Shopee e-commerce). The type of research used is research with a conclusive design, namely a type of inferential research which aims to test a certain hypothesis, either through in-depth research into a problem (descriptive) or looking for relationships between variables (correlative) between the independent variable and the dependent variable. The research results show that brand image has a positive and insignificant effect on customer satisfaction. Brand image has a positive and insignificant effect on customer loyalty. Product quality has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and insignificant effect on customer loyalty. Brand image has a positive and insignificant indirect effect on customer loyalty through customer satisfaction. Product quality has a positive and insignificant indirect effect on customer loyalty through customer satisfaction.